2018
DOI: 10.5530/jyp.2019.11.14
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Success Rate of Directly Observed Treatment Short-Course (DOTS) in Tuberculosis Patients of South India

Abstract: Objective: To assess the success rate of DOTS for tuberculosis patients and the secondary objective was to identify the factors associated with unsuccessful treatment outcome. Methods: A retrospective study was conducted to review the medical records of patients (n = 1113) registered at the Directly Observed Treatment Short-Course (DOTS) clinic of Government Infectious Disease (Govt. ID) Hospital, Guntur, India. Multivariate logistic regression model was used to determine the factors associated with the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…A study in Kelantan showed that HIV was strongly associated with unsuccessful treatment outcome [3]. Other studies also showed a similar finding [16][17][18]. HIV tends to weaken the immune system.…”
Section: Discussionmentioning
confidence: 83%
“…A study in Kelantan showed that HIV was strongly associated with unsuccessful treatment outcome [3]. Other studies also showed a similar finding [16][17][18]. HIV tends to weaken the immune system.…”
Section: Discussionmentioning
confidence: 83%
“…Undernutrition-defined as weight <35kg [134] or baseline weight less than the median for the cohort [86]-was associated with increased adjusted risk of unfavorable outcomes. People with HIV, or with unknown HIV status, had higher adjusted risk of unfavorable outcomes, as compared to people without HIV in 3 studies [86,130,132]. Unknown diabetes status (versus not having diabetes) was also associated with unfavorable outcomes in 1 adjusted analysis [130].…”
Section: Factors Associated With Unfavorable Tb Treatment Outcomes In...mentioning
confidence: 97%
“…Given numerous studies for this subgroup, we only describe findings from adjusted analyses; findings from unadjusted analyses are reported in Table D4 in S4 Appendix. With regard to patient-, family-, or society-related factors, male sex was associated with unfavorable outcomes in 8 adjusted analyses [43,44,86,[128][129][130][131][132] (Fig 19). In 7 adjusted analyses, older age was associated with unfavorable outcomes across a range of age thresholds [86,89,91,129,130,133,134].…”
Section: Factors Associated With Unfavorable Tb Treatment Outcomes In...mentioning
confidence: 99%
See 2 more Smart Citations